Transcranial stimulation over the left inferior frontal gyrus increases false alarms in an associative memory task in older adults - Leach, Ryan C. (Healthy Aging Res, 2016)
BACKGROUND: Transcranial direct current stimulation (tDCS) is a potential tool for alleviating various forms of cognitive decline, including memory loss, in older adults. However, past effects of tDCS on cognitive ability have been mixed. One important potential moderator of tDCS effects is the baseline level of cognitive performance. METHODS: We tested the effects of tDCS on face-name associative memory in older adults, who suffer from performance deficits in this task relative to younger adults. Stimulation was applied to the left inferior prefrontal cortex during encoding of face-name pairs, and memory was assessed with both a recognition and recall task. RESULTS: Face–name memory performance was decreased with the use of tDCS. This result was driven by increased false alarms when recognizing rearranged face–name pairs. CONCLUSIONS: This result suggests that tDCS can lead to increased false alarm rates in recognition memory, and that effects of tDCS on a specific cognitive task may depend upon cognitive capability for that task.